Grateful Personality Development of Junior High School Students in East Kalimantan - Nur Kholik Afandi; Syatria Adymas Pranajaya (Southeast Asian Journal of Islamic Education, 2022)
A grateful personality is one of the essential elements in the personality development of students. This personality is reflected in verbal and deeds as a manifestation of acknowledgment in the heart for the blessings. This personality encourages students to appreciate and repay the kindness of others. This study aims to determine the level of gratitude of junior high school students in East Kalimantan. This study used a mixed-method approach. Respondents in this study were 714 people. The mean test results showed that the level of students' gratitude at Junior High Schools in East Kalimantan was very high, with an average score of 4.6. The teacher's strategies in instilling a grateful personality are with advice, exemplary, assignments, habituation, and activity programs at school. The methods are by providing materials (lectures, advice, discussions, and questions and answers related to gratitude), exemplary by providing examples of the values of gratitude, giving demonstration tasks, and practice in gratitude, giving the task of making a list of good things that have been felt and should be grateful for every day, habituation to good things (instilling the nature of qana'ah, giving appreciation and motivation, presenting a sense of empathy around oneself, inviting self-introspection, giving charity, helping others, spreading smiles, greetings, visiting friends or teachers who are sick or grieving), and school programs (dhuha and dzuhur prayers in congregation, reading the Qur'an, praying before starting lessons, and giving sadaqah every Friday at school). The results of this study may have an implication to become a policy regulation for schools to support the development of a grateful personality for students of Junior High School.